Prevalence of Extended Spectrum b-Lactamases (ESBL) Producers Among Gram-Negative Bacilli in Wound Infection - Karim Chowdhury, Abu Hena Md Saiful; Husain, Md Anwar; Akter, Nasima; Alam, Khan Mashrequl; Dewanjee, Arup Kanti; Ahmed, Shakeel; Hossain, Zakir; Rahman, Arifur; Naheen, Towhida; Mazed, Md Abdul; Biswas, Sanjoy Kanti; Hoque, Md Ehsanul (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2016)
Background: Extended Spectrum b -Lactameses Producing Organisms (ESBLs) are increasing in number and causing more severe infections because of their continuous mutation and multidrug resistance property with limited therapeutic option. Aims and Objectives: Present study was undertaken to detect the prevalence of the ESBLs producing bacteria in wound infection, so as to provide a base line data in treating them & prevent unnecessary use of antibiotics Methods: Isolated gram-negative bacteria initially screened by Minimum Inhibitory Concentration (MIC) ESBLs breakpoints. Then suspected ESBLs producers were confirmed by Phenotypic confirmatory test. Results: 105 (One hundred five) (91.30%) bacterial strains were isolated from 115 samples of wound swab & pus from different patients were studied of which 84(80.00%) were Gram-negative and 21(20.00%) were Gram-positive. Among the isolated Gram-negative bacteria 79(94.05%) were found suspected ESBLs producers of which 54(68.35%) were found as confirmed ESBL producers. The prevalence of ESBLs producing organisms in the present study were found to be 64.29% and Klebsiella spp as most prevalent ESBLs producers. Conclusion: It is essential to report ESBL production along with routine sensitivity reporting, which will help the clinician in prescribing the proper antibiotics. Chatt Shi Hosp Med Coll J; Vol.15 (1); Jan 2016; Page 26-30